Cultural autonomy and political participation - Dobos, Bala??zs, 1980- author. Link
1 online resource.
Keywords: "This book provides a comparative, theoretical and empirical understanding of the possible role of elections to minority councils and self-governments, local variants of national-cultural autonomy bodies in five East-Central European countries. The functions and effects of elections serve as analytical tools that enable the book to provide a realistic overview of minority political participation in this particular institutional channel and empirical evidence on the extent to which existing normative expectations towards national-cultural autonomy are met within these arrangements. Using the elections of cultural autonomous bodies in Croatia, Estonia, Hungary, Serbia and Slovenia as examples, the book examines how these rather understudied institutions specific to minority councils and self-governments affect the lives of national and ethnic minorities, how they approach them and how they are established in each country. In the post-Communist environment that fundamentally rejects autonomy, these organizations are still officially referred to as autonomies, whereas they often function more like consultative-advisory bodies. The book traces this process from the adoption of autonomy, through the polling booth, to the operational level, without avoiding sensitive issues raised by these autonomies, such as what is commonly known as ethno-business. Focusing on topical issues such as minority representation and participation, the book will be of interest to a broad group of international academics, researchers and policy-makers working in the areas of Minority Studies, Legal Studies, Political Science and Anthropology"--